Proses Manajemen Pengetahuan Bagi Inovasi Pelayanan Perizinan di Kota Yogyakarta - NURMANDI, ACHMAD (Universitas Muhammadiyah Yogyakarta, 2010)
Innovation in government organization through managing knowledge is important current research results. This research objective were to look at knowledge management in improving public services, particularly in public licencing process. Research problem was how sense making, knowledgecreating and knowledge sharing in public licencing services of Yogyakarta city. Research found that knowledge sharing and creating took place in midlle and bottom of organization level. Stages of innovation at the Licensing Agency began with the formulation of the problem, which consists of thousands of service files can not be known with certainty the level of completion. In the next stage, a member organization consisting of experienced employees who tried to solve by making the development of information systems. Licensing Office of the types of organizations can be categorized as a deliberative democracy 'adhocracy' an organization with the type of environment, where there is high public participation and concern in the licensing service.Keyword: Innovation, Knowledge sharing, Knowledge creation, AutonomyDOI: http://dx.doi.org/ 10.18196/jgp.2010.0002